PENGARUH MOTIVASI, KOMPENSASI, DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Lie, Christoffer; Gulo, Yupiter (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study is to analyze the influence of motivation, compensation and organizational commitment on organizational citizenship behavior. The object used in this study is Dealer Yamaha Flagship Shop Cempaka Putih Jakarta. Sampling using probability sampling technique with a total sample used as many as 71 respondents. The study was analyzed using statistical software programs. The analytical method used is multiple linear regression. The technique of collecting data is by distributing questionnaires using a Likert scale. Based on the results of the hypothesis test data analysis in this study, it shows that motivation has a negative significant effect on organizational citizenship behavior, compensation has a positive significant effect on organizational citizenship behavior, and organizational commitment has a positive significant effect on organizational citizenship behavior.